Online Learning as a Catalyst for Self-directed Learning in Universities during the COVID-19 Pandemic - Mncedisi Christian Maphalala; Rachel Gugu Mkhasibe; Dumisani Wilfred Mncube (Research in Social Sciences and Technology- OpenED Network, 2021)
The COVID-19 pandemic accelerated the use of online learning and self-directed learning to motivate and engage students. Therefore, this study sought to determine how online learning fostered self-directed learning at a South African university during this period. Higher education institutions worldwide had to shut down indefinitely following guidance from health experts to contain the spread of the COVID-19 pandemic. Since education is regarded as a pillar of development for all countries, some means had to be found to keep teaching and learning going irrespective of the ongoing health crisis. Hence, online learning made it possible for university students to continue learning during the emergency university closure. This was a period of reckoning, however, as many students began experiencing challenges related to poor internet connectivity and accessing digital learning devices. Despite these challenges, the solution was to reach out to all students to ensure that they were not excluded from the learning process. The sudden transition to online learning meant that students could no longer follow a well-coordinated, structured learning schedule that was guided and supervised on campus; rather, online learning meant they had to become more independent in their learning. Independent learning encourages students to be proactive and independent, a philosophy aligned to self-directed learning (SDL). This study explored the experiences of third-year student teachers in navigating SDL through online learning platforms. The study was underpinned by self-directed learning theory and adopted a qualitative case study research design, generating data from ten student teachers using a Zoom App focus group discussion. Data were analyzed using an inductive thematic analysis framework. The study found that although SDL is appropriate because it promotes learning independently, the majority of student teachers encountered several challenges when adopting online learning, catching them off guard because they were not formally introduced to it.